2004
DOI: 10.1017/s1367943003001173
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary evaluation of the sustainability of cassowary (Aves: Casuariidae) capture and trade in Papua New Guinea

Abstract: Wildlife capture and trade for traditional use in Papua New Guinea has led to the extirpation of cassowary in some areas and increasing pressure for trade from areas where they remain. We tested a village-based monitoring programme to evaluate sustainability of wildlife capture and trade by households in the Crater Mountain Wildlife Management Area. We monitored the type and number of wildlife species captured and traded. For the most heavily traded species, dwarf cassowary, we compared estimated annual offtak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 21 publications
2
17
0
Order By: Relevance
“…This finding has significant implications for cassowary management strategies in Australia, and also in New Guinea, where cassowaries are traditionally harvested for subsistence and trade. In an evaluation of the sustainability of dwarf cassowary Casuarius bennetti capture and trade in Papua New Guinea (Johnson et al 2004), the carrying capacity (K) was calculated from studies of dwarf cassowary abundance (Mack 1995;Mack and Wright 1996), and population densities reported for the southern cassowary (Crome and Bentrupperbäumer 1991). The New Guinea study concluded that live offtake rates of 0.06-0.07/birds km 2 were unsustainable or near unsustainable in the management areas studied.…”
Section: Revised Density Estimates and Cassowary Management In Austramentioning
confidence: 99%
“…This finding has significant implications for cassowary management strategies in Australia, and also in New Guinea, where cassowaries are traditionally harvested for subsistence and trade. In an evaluation of the sustainability of dwarf cassowary Casuarius bennetti capture and trade in Papua New Guinea (Johnson et al 2004), the carrying capacity (K) was calculated from studies of dwarf cassowary abundance (Mack 1995;Mack and Wright 1996), and population densities reported for the southern cassowary (Crome and Bentrupperbäumer 1991). The New Guinea study concluded that live offtake rates of 0.06-0.07/birds km 2 were unsustainable or near unsustainable in the management areas studied.…”
Section: Revised Density Estimates and Cassowary Management In Austramentioning
confidence: 99%
“…et al In Papua New Guinea (PNG) many different species are hunted across a variety of ethnic groups, in local PNG dialect, including the (large mammals), the (small sab honez mammals), the (birds). Other game species also hunted sort include (frogs), (fish) and the occasional large jiya wen reptile, notably (pythons), and they are all (edible burun acha fauna) (Dwyer 1983;Sillitoe 2001;Johnson . 2004;et al Mack & West 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Recent analyses of hunting and capture rates, combined with estimates of population densities and rates of increase, have shown that offtake rates of cassowaries and several frequently killed medium-sized mammals are unsustainable (Johnson et al 2004;Cuthbert 2010). Not surprisingly, 11 of the 14 species of tree-kangaroos (Dendrolagus spp.…”
Section: Introductionmentioning
confidence: 99%